1995
DOI: 10.1037/0097-7403.21.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Responses to quantity: Perceptual versus cognitive mechanisms in chimpanzees (Pan troglodytes).

Abstract: Two chimpanzees were trained to select among 2 different amounts of candy (1-6 items). The task was designed so that selection of either array by the active (selector) chimpanzee resulted in that array being given to the passive (observer) animal, with the remaining (nonselected) array going to the selector. Neither animal was able to select consistently the smaller array, which would reap the larger reward. Rather, both animals preferentially selected the larger array, thereby receiving the smaller number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
349
12
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 264 publications
(398 citation statements)
references
References 7 publications
35
349
12
2
Order By: Relevance
“…Does the reverse reward task test for "self control"? Initially, studies on impulse control were mainly performed with humans (Mischel et al 1989;Russell et al 1991) and primates (Boysen and Berntson 1995;Boysen et al 1996;Silberberg and Fujita 1996;Kralik et al 2002;Genty et al 2004). Some authors have suggested that success in the reverse reward task may be interpreted as a form of "self control" thereby implying that in order to solve the task, some "awareness of self" needs to be involved (e.g.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Does the reverse reward task test for "self control"? Initially, studies on impulse control were mainly performed with humans (Mischel et al 1989;Russell et al 1991) and primates (Boysen and Berntson 1995;Boysen et al 1996;Silberberg and Fujita 1996;Kralik et al 2002;Genty et al 2004). Some authors have suggested that success in the reverse reward task may be interpreted as a form of "self control" thereby implying that in order to solve the task, some "awareness of self" needs to be involved (e.g.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Finally, after the surprising Wnding that many primates have diYculties in refraining from the larger amount in order to obtain a small one (Boysen and Berntson 1995), many subsequent studies focussed on procedures that help the test subjects to overcome this problem. However, this approach may distract from an important question, i.e.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 3 more Smart Citations